2021
DOI: 10.1097/shk.0000000000001822
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect of Systemic Steroids in Patients with Cirrhosis and Septic Shock

Abstract: Evidence regarding the utility of systemic steroids in treating patients with cirrhosis and septic shock remains equivocal. This study aimed to evaluate and elucidate the association of steroid use with outcomes and adverse effects in a cohort of patients with cirrhosis and septic shock. Patients and methods: Retrospective cohort study of patients with cirrhosis and septic shock admitted to a tertiary hospital intensive care unit (ICU) from January 2007 to May 2017, using a validated ICU Datamart. Patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Corticosteroids: Arabi et al [ 13 ] concluded that corticosteroids improved the hemodynamic status of the patient but did not change mortality (Table 1 ). Rinaldi et al [ 5 ] and Piccolo Serafim et al [ 14 ] found similar results to Arabi et al [ 13 ] (Tables 2 and 3 ).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Corticosteroids: Arabi et al [ 13 ] concluded that corticosteroids improved the hemodynamic status of the patient but did not change mortality (Table 1 ). Rinaldi et al [ 5 ] and Piccolo Serafim et al [ 14 ] found similar results to Arabi et al [ 13 ] (Tables 2 and 3 ).…”
Section: Resultssupporting
confidence: 77%
“…Nevertheless, its use in liver cirrhosis remains controversial[ 7 ]. Hydrocortisone improves the hemodynamic status of the patient without a relevant change in mortality[ 13 , 14 , 18 ]. Hydrocortisone is associated with better shock resolution, although without an impact on survival[ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients treated in the corticosteroid arm had a higher incidence of shock relapse, which supports the notion of unmasked RAI. A higher incidence of gastrointestinal bleeding was observed in the Arabi trial, but this was not replicated in larger observational studies[ 146 ]. Despite the mixed evidence, SSC guidelines currently recommend the use of corticosteroids in patients with refractory shock[ 45 ].…”
Section: Adrenal Dysfunctionmentioning
confidence: 99%
“…A retrospective cohort study demonstrated that use of systemic corticosteroids in patients with cirrhosis and septic shock was not found to reduce mortality or length of ICU and hospital stay. 93 A large, multicenter trial found that hydrocortisone alone did not reduce mortality compared with placebo, 94 while another study found the combination of hydrocortisone and fludrocortisone to improve 90-day survival in septic shock. 95 Although corticosteroids' general role in shock resuscitation remains undefined, their use in the setting of relative adrenal insufficiency should be entertained and will be discussed later.…”
Section: Cardiovascularmentioning
confidence: 99%